HUMAN RESOURCE DEVELOPMENT OF PRIVATE SCHOOLS IN THE SYSTEM UNDER THE OFFICE OF EDUCATION PHICHIT PROVINCE - Suebjaitha, Phonnapha; Wongwatthanaphong, Kampanart; Dokchan, Pasakorn (Journal of MCU Phetchaburi Review, 2025)
This research aimed to 1) study the level of human resource development in private schools, 2) compare the level of human resource development in private schools, and 3) suggest guidelines for human resource development in private schools in the system under the Office of the Provincial Education, Phichit. The research methodology was quantitative research. The sample group was 244 personnel of private schools in the system under the Office of the Provincial Education, Phichit. The research instrument was a questionnaire. The statistics used were frequency, percentage, mean, standard deviation, t-test, F-test, The research results showed that 1) the level of human resource development in private schools in the system, overall and in each aspect, was at a high level. 2) Personnel with different ages, education levels, positions, and length of service had different opinions on the level of human resource development in private schools in the system, with statistical significance at the .05 level. And 3) Suggested guidelines for human resource development are self-development training should be provided according to the curriculum of the subject matter that is in line with the subject matter group or can be applied to actual work. Teachers should be able to continue their studies at a higher level.